Social sphere development regularities in regional reproduction in Russia - Nikolay N. Reutov, Viktoriya V. Chirkova, Igor E. Rovenskikh, Tamara P. Belikova, Tatyana A. Syrovatskaya, (Opción, 2019)
The article is devoted to the theoretical analysis of social enterprise development in the reproduction process. As a method, the social sphere has analyzed the system of enterprise effective functioning. As a result, one of the key tasks of the regional reproduction process improvement is the effective development of the social sphere. In conclusion, a necessary condition for the rational combination of sectoral and regional aspects of social infrastructure development planning is the division of the country territory into regions.